Genistein is effective in inhibiting Orf virus infection in vitro by targeting viral RNA polymerase subunit RPO30 protein - Lv, Pin; Fang, Ziyu; Guan, Jiyu; Lv, Lijun; Xu, Mengshi; Liu, Xingyuan; Li, Zhuomei; Lan, Yungang; Li, Zi; Lu, Huijun; Song, Deguang; He, Wenqi; et al. (Frontiers in Microbiology, 2024)
Orf virus (ORFV), a typical member of the Parapoxvirus genus, Poxvirus family, causes a contagious pustular dermatitis in sheep, goats, and humans. Poxviruses encode a multisubunit DNA-dependent RNA polymerase (vRNAP) that carries out viral gene expression in the host cytoplasm, which is a viral factor essential to poxvirus replication. Due to its vital role in viral life, vRNAP has emerged as one of the potential drug targets. In the present study, we investigated the antiviral effect of genistein against ORFV infection. We determined that the viral genome DNA transcription/replication levels as well as viral protein synthesis were dose-dependently decreased in genistein-treated cells. Furthermore, we identified that genistein interacted with the vRNAP RPO30 protein, a novel antiviral target for ORFV. By blocking vRNAP RPO30 protein using antibody against RPO30, we confirmed the inhibitory effect exerted by genistein against ORFV infection is mediated through the interaction with RPO30. In conclusion, we demonstrate that genistein effectively inhibits ORFV transcription in host cells by targeting vRNAP RPO30, which might be a promising drug candidate against poxvirus infection.